Classification system of stress-associated and post-traumatic stress disorders and its justification - Danyk, Yuriy; Druz, Oleg; Chernenko, Inna (Journal of Education, Health and Sport, 2017)
The objective: to form classification of stress- associative and post-traumatic stress disorders on the base of analysis of their existing theoretical and empirical studies. Through the use of a content analysis of theoretical and empirical studies, the features of the formation and development of various manifestations of post-traumatic personality stress disorders and combat mental trauma are considered. A holistic classification of post-traumatic stress disorders is proposed, depending on: the variant and stage of development, the type of course, clinical or psychological manifestations, the time of the course, the results and degrees of severity. It has been established that the development of post-traumatic stress disorders affects: the duration of a crisis situation, terrain, primorbid, history of life, the type of individual reaction to the crisis situation itself, the motivation of which the soldier consciously (or unconsciously) goes to war, micro and macrosocium, information effects, the influence of the media, individual experience gained, both practical and theoretical, social and psychological support, the influence of chemical agents (drugs, chemical ix). The final stage of the development of post-traumatic stress disorders may be the formation of post-traumatic personality disorder, as its extreme manifestation